2020
DOI: 10.1111/and.13778
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil‐induced ion channel and miRNA expression changes in rat testis and/or spermatozoa may be associated with male infertility

Abstract: Verapamil, a prototypical phenylalkylamine, is the clinically first used Ca 2+ channel blocker (CCB). It is known to be an effective drug in the treatment of hypertension (Bergson, Lipkind, Lee, Duban, & Hanck, 2011). However, due to the fact that an ion channel type is often expressed in many cell types, an important side effect of such drugs may occur negatively affecting normal function in nondiseased tissues (Conte Camerino & Desaphy, 2010). Mature spermatozoa are produced in spermatogenesis which is a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We did not evaluate the sperm concentration, motility and morphology (Tektemur et al, 2020), vitality (Banihani & Shatnawi, 2020 as in the previous studies, but found an important finding which is a reduced mean sperm numbers may occur following the spinal SAH. The histological view of seminiferous tubules of a control group animal in Figure 4a, and atrophic seminiferous tubules with deformed spermatids and apoptotic spermatids and constructed-oedematous testicular artery of a rabbit with SAH are seen in Figure 4c.…”
Section: Limitation Of the Studymentioning
confidence: 88%
“…We did not evaluate the sperm concentration, motility and morphology (Tektemur et al, 2020), vitality (Banihani & Shatnawi, 2020 as in the previous studies, but found an important finding which is a reduced mean sperm numbers may occur following the spinal SAH. The histological view of seminiferous tubules of a control group animal in Figure 4a, and atrophic seminiferous tubules with deformed spermatids and apoptotic spermatids and constructed-oedematous testicular artery of a rabbit with SAH are seen in Figure 4c.…”
Section: Limitation Of the Studymentioning
confidence: 88%
“…Calcium ions are vital second messengers in human physiology, and the use of drugs that interfere with their function may potentially lead to an interference with a number of biological pathways, thus including spermatogenesis. Even though reduced sperm concentration, impaired serum testosterone, FSH and LH levels were associated with verapamil exposure in a number of preclinical studies on rats [71,72], well-designed observational studies and RCTs to define this association in the clinical setting are still lacking. Calcium channels are highly represented in mature sperm cells, and interference with these may potentially lead to an interference with some of the sperm-egg fertilization processes, such as the acrosome reaction [71].…”
Section: Discussionmentioning
confidence: 99%
“…Even though reduced sperm concentration, impaired serum testosterone, FSH and LH levels were associated with verapamil exposure in a number of preclinical studies on rats [71,72], well-designed observational studies and RCTs to define this association in the clinical setting are still lacking. Calcium channels are highly represented in mature sperm cells, and interference with these may potentially lead to an interference with some of the sperm-egg fertilization processes, such as the acrosome reaction [71]. Calcium ions are also needed for the epididymal acquisition of sperm motility in experimental models [73].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that paternal obesity and dietary changes contribute crucially to miRNA dysregulation in spermatozoa, which may also further dictate offspring metabolism [ 9 , 10 ]. Similarly, alterations in miRNA expression, associated with decreased fertility in males, have been determined in sperm and seminal plasma from patients using prescription drugs and illegal substances, including verapamil [ 11 ] and heroin [ 12 ], respectively. In addition, a study by Jia et al on animal models discovered miRNAs the expression profiles of which differed in relation to the age of the animals [ 13 ], which suggested that such interrelations could also apply in humans.…”
Section: Introductionmentioning
confidence: 99%